A Critical Appraisal of Virtual Reconstructions in Archaeology - Cleland, Aoife (2024)
Archaeology will always be a partially imagined account of the past based on fragmentary evidence. Since the beginnings of the discipline, archaeologists have used artistic visualisations to create and communicate hypothetical holistic views of the past – virtual reconstructions (VRs) are the latest technique to be developed. Since their creation in the 1980’s, VRs have constantly evolved with the development of technology, providing more opportunities for archaeologists to engage a wider audience in their cultural past. Forte and Murteria (2020) argue that VRs have changed our relationship with the past; they have made the past more active, immersive and personal, allowing viewers to ‘inhabit’ ancient spaces (Forte 2005). Technology has also changed how archaeologists operate; Morgan (2022) suggests its impact can be seen in how archaeologists perceive the past and disseminate those interpretations. ‘VR’ in the context of this present work will refer to a computer-based 3D digital model of a past historical environment. The VRs in this thesis can be found in museums/heritage attractions or within peer-reviewed scholarly work.